1962
DOI: 10.6028/jres.066a.037
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate phases in superconducting niobium-tin alloys

Abstract: (April 13, 1(62) .In attempting to produ ce s up erconducting " 'ire of t he niobium sheath Nb, n core type, It became app arent t h a~ r es ults were genera lly unpredictable. Metallographic examination s how~d t hat s uch matenals arc het erogeneous and contain a number of interm ediate phases. DetaIled metallographlC studies we re made on diffusion zones in which t in h ad been allowed to react with porous niobium blocks, with fu sed niobium rod, and with niobium wires, and on a number of reacted po\\"de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1963
1963
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…Single-phase, f3-tungsten structure deposits on wire and ribbon substrates had compositions ranging between 76.2 and 81.5 atomic percent niobium because of changing conditions in the deposition process. This composition range is in a close agreement with the phase diagram proposed by Wyman et al (1962), who have shown that in the niobium-tin system above 863C only one compound exists with very nearly the same composition range as that given above.…”
Section: E Physical Properties and Chemical Analysissupporting
confidence: 80%
“…Single-phase, f3-tungsten structure deposits on wire and ribbon substrates had compositions ranging between 76.2 and 81.5 atomic percent niobium because of changing conditions in the deposition process. This composition range is in a close agreement with the phase diagram proposed by Wyman et al (1962), who have shown that in the niobium-tin system above 863C only one compound exists with very nearly the same composition range as that given above.…”
Section: E Physical Properties and Chemical Analysissupporting
confidence: 80%
“…The specimens presently under investigation by quantitative m etallography are part of a series of diffusion specimens and reacted powder mLxtures which have been under investigation by a number of methods in an effort to establish the phase diagram of the Nb-Sn system and to determine the most effective method of preparing the NbaSn phase [8].…”
Section: Niobium-tin Alloy Systemmentioning
confidence: 99%
“…The colors produced on different metallographic constituents vary somewhat with the degree of anodization, and can be deliberately varied to aid in distinguishing phase areas. On the basis of microspot spectrochemical analyses of characteristic areas, the constituents in the microstructures have been tentatively identified [8] as shown in table 2.…”
Section: Niobium-tin Alloy Systemmentioning
confidence: 99%